Capillary leak syndrome following COVID-19 vaccination: Data from the European pharmacovigilance database Eudravigilance - Ruggiero, Rosanna; Balzano, Nunzia; Di Napoli, Raffaella; Mascolo, Annamaria; Berrino, Pasquale Maria; Rafaniello, Concetta; Sportiello, Liberata; Rossi, Francesco; Capuano, Annalisa (Frontiers in Immunology, 2022)
Capillary leak syndrome (CLS) emerged as new adverse event after immunization (AEFI) associated to COVID-19 vaccination. CLS is a rare condition characterized by increased capillary permeability, resulting in hypoalbuminemia, hypotension, and edema mainly in the upper and lower limbs. Our pharmacovigilance study aims to evaluate the CLS onset following receipt of COVID-19 mRNA vaccines (mRNA-1273 and BNT162b2) compared to viral vector vaccines (Ad26.COV2-S and ChAdOx1-SARS-COV-2). We carried a cross-sectional study using all Individual Case Safety Reports (ICSRs) reporting a COVID-19 vaccine as suspected drug and CLS as AEFI, which were collected in the pharmacovigilance database EudraVigilance from January 1st, 2021, to January 14th, 2022. We applied the Reporting Odds Ratio (ROR) 95% CI for the disproportionality analysis. During our study period, CLS was described as AEFI in 84 out of 1,357,962 ICRs reporting a vaccine COVID-19 as suspected drug and collected in the EV database. Overall, the ICSR reported by CLS were mainly related to the viral vector COVID-19(ChAdOx1-SARS-COV-2 = 36; Ad26.COV2-S = 9). The mRNA COVID-19 vaccines were reported in 39 ICSRs (BNT162b2 =33; mRNA-1273 =6). Majority of ICSRs were reported by healthcare professionals (71.4%). Majority of the patients were adult (58.3%) and the female gender accounted in more than 65% of ICSRs referred both to classes vaccines. In particular, women were more represented in ICSRs referred to mRNA-1273 (83.3%) and to ChAdOx1-SARS-COV-2 (72.2%). The CLS outcome was more frequently favorable in mRNA ICSRs (33,3%) than the viral vector ones (13.3%). Among the ICSRs reporting CLS with unfavorable outcome, we found also 9 fatal cases (BNT162b2 = 1; ChAdOx1-SARS-COV-2 = 4; Ad26.COV2-S = 4). From disproportionality analysis emerged a lower CLS reporting probability after vaccination with mRNA vaccines compared to viral vector-based ones (ROR 0.5, 95% CI 0.3–0.7; p <0.001).Our findings, even if subject to the limitations of spontaneous reporting systems, suggest a small but statistically significant safety concern for CLS following receipt of COVID-19 viral vector vaccines, in particular with Ad26.COV2-S. Cytokine-release following T-cell activation could be involved in CLS occurrence, but a precise mechanism has been not yet identified. COVID-19 vaccines remain attentive as possible CLS triggers.